Effectiveness of Desa Siaga-Alert Village Programs for Empowerment of Self-Independent Communities Case Study: Desa Siaga Rabies-Rabies Alert Villag of Martajaya Village, Pasangkayu District - Farida, Umi; ., Ansar; Bata Ilyas, Gunawan; ., Jamaludin; Sahabudin, Chuduriah (International Journal of Engineering and Technology, 2018)
The concept of Desa Siaga is to build one system in a village that is responsible for the health of the community itself. Desa Siaga encourages people to have the ability and initiative to respond immediately. The aim of the study will review the problem of how effective the Desa Siaga RabiesÂ program is for independent healthy community empowerment in Martajaya Village, Pasangkayu District. The results of the study show that the implementation of the Desa Siaga Rabies program has run quite well, but it cannot be said to be effective for the empowerment of independent healthy communities..Â Â Â